Respuesta :
Simplify 2y - 10 - 2 to 2y - 10 :
4y=2y−12
Than subtract 2y from sides:
4y − 2y = −12
Simplify 4y−2y to 2y
2y = −12
Divide both sides by 2
[tex]- \frac{12}{2} [/tex] simplify it to 6
y = −6 should be your final answer
4y=2y−12
Than subtract 2y from sides:
4y − 2y = −12
Simplify 4y−2y to 2y
2y = −12
Divide both sides by 2
[tex]- \frac{12}{2} [/tex] simplify it to 6
y = −6 should be your final answer
1. Use the distributive property on 2(y-5)
4y = 2(y-5)-2 --> 4y = 2y - 10 -2
2. Add the like terms together
4y = 2y - 10 - 2 --> 4y = 2y - 12
3. Use the Subtraction Property of Equality
4y = 2y - 12 --> 2y = -12
4. Use the Division Property of Equality
2y = -12/2 /2
y= -6
Hope this helps!!! :D
4y = 2(y-5)-2 --> 4y = 2y - 10 -2
2. Add the like terms together
4y = 2y - 10 - 2 --> 4y = 2y - 12
3. Use the Subtraction Property of Equality
4y = 2y - 12 --> 2y = -12
4. Use the Division Property of Equality
2y = -12/2 /2
y= -6
Hope this helps!!! :D